Zwischen Mensch und Modell Essays rund um die Humanembryologische Dokumentationssammlung Blechschmidt - Domdey, Anna; Iffert, Corinne Astrid; Krahl, Jakob; Walter, Denise Simone (Universitätsverlag Göttingen, 2021)
The Blechschmidt collection is a collection of medical preparations used primarily for teaching purposes. Consisting of 61 models of embryos, it is located at the Institute for Anatomy of the Medical Faculty of Göttingen University. Over the course of the summer semester 2019 and the winter semester 2019/2020 a group of cultural anthropology students conceptualized a special exhibition highlighting history, provenance and social relevance of Blechschmidt collection and exhibition. This volume contains essays by the students involved, that resulted out of scientific discourse and research revolving around the Blechschmidt collection.